On food security stocks, peace clauses, and permanent solutions after Bali - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2014)
This paper discusses potential solutions to the current impasse related to food security stocks, including a concrete proposal by the author on language to be included in the Agreement on Agriculture that may help comply with the mandate of the Bali Ministerial to find a solution in the next four years. The paper begins with an explanation of the background to the debate of the links between food security and WTO agricultural and trade negotiations and the interim solution (the peace clause) agreed upon at Bali. Then it discusses some economic issues that frame the discussion about food security stocks, noting the new context of higher (in nominal terms) and perhaps more volatile food prices, in part associated with expanding links among energy markets and food production, supply and prices, and greater weather variability associated with climate change. The paper analyzes potential approaches to solving the problems related to the use of public stocks for food security reasons and suggests specific language that may solve the current debate. The paper also notes the more complex political economy of the future negotiations, which, among other things, will require greater flexibility among WTO Member s and deeper awareness of the evolving negotiating landscape.